Experimental respiratory infection of goats with Mycoplasma arginini and Pasteurella haemolytica A2 - Saad, Mohd Zamri; A., Azri; A. B., Nurida; Abdul Rahman, Sheikh Omar (Universiti Pertanian Malaysia Press, 1994)
Twenty-one healthy local goats of about eight months old were divided into four groups consisting of six animals in groups 1, 2 and 3 and three animals in group 4. Goats in groups 1 and 2 were inoculated intratracheally with Mycoplasma arginini. Goats in group 2 were inoculated again with Pasteurella haemolytica A2 six days later. Goats in group 3 were inoculated intratracheally with P. haemolytica A2 alone while goats in group 4 received intratracheal inoculation ofPBS. The goats were euthanised at day 1, 3 and 7 post inoculation with P. haemolytica. Four goats in group 1 and three goats in group 3 had small patches of mild pneumonic lesions. Goats in group 2 had severe lung lesions typical of pneumonic pasteurellosis at the anteroventral region of the lungs. None of the goats in group 4 had pulmonary lesions. P. haemolytica was reisolated from all goats in group 2 and from three goats in group 3 but M. arginini was not reisolated.